Ozone therapy in medicine and dentistry - Nogales, Carlos Goes; Ferrari, Patricia Helena [UNESP]; Kantorovich, Efraim Olszewer; Lage-Marques, José (My University, 2008)
Aim: The purpose of this review is to present the potential for the incorporation of ozone therapy into the practice of dentistry. Background: Ozone gas has a high oxidation potential and is 1.5 times greater than chloride when used as an antimicrobial agent against bacteria, viruses, fungi, and protozoa. It also has the capacity to stimulate blood circulation and the immune response. Such features justify the current interest in its application in medicine and dentistry and have been indicated for the treatment of 260 different pathologies. It can be used for the treatment of alveolitis as a replacement for antibiotic therapy, as a mouthwash for reducing the oral microflora, as well as the adherence of microorganisms to tooth surfaces. Ozone has been shown to stimulate remineralization of recent caries-affected teeth after a period of about six to eight weeks. Conclusion: The future of ozone therapy must focus on the establishment of safe and well-defined parameters in accordance with randomized, controlled trials to determine the precise indications and guidelines in order to treat various medical and dental pathologies. Scientific support, as suggested by demonstrated studies, for ozone therapy presents a potential for an atraumatic, biologically-based treatment for conditions encountered in dental practice.
Keywords: Ozonated water; Ozone; Ozone therapy